Posterior mediastinal goiters: Report of two cases and literature review - Samokhvalov, Alexander (Elsevier, 2011)
Intrathoracic goiters represent substantial enlargement and descent of cervical thyroid tissue into the thoracic cavity, usually in the anterior mediastinum. Rarely, they extend posteriorly, causing obstructive symptoms, sometimes with acute onset. Posterior mediastinal goiters should be differentiated from other mediastinal masses by appropriate work-up, while computed tomography is the most valuable technique. We report two cases of such symptomatic goiters. First reported case was atypically presented with aspiration pneumonia and second was successfully operated. Our overview aims to increase awareness of this rare clinical entity due to possible respiratory compromise. Reasonable surgical management is mandatory.